1999
DOI: 10.1016/s0014-5793(99)01477-5
|View full text |Cite
|
Sign up to set email alerts
|

Up‐regulation of uncoupling protein 3 by thyroid hormone, peroxisome proliferator‐activated receptor ligands and 9‐cis retinoic acid in L6 myotubes

Abstract: Uncoupling protein 3 (UCP3), expressed abundantly in the skeletal muscle, is one of the carrier proteins dissipating the transmitochondrial electrochemical gradient as heat, and thereby has been implicated in the regulation of energy metabolism. We have investigated UCP3 mRNA expression in the widely used L6 myocyte cell line by Northern blot analysis. UCP3 mRNA was not detected in L6 myoblasts, but appeared after their differentiation to myotubes. The UCP3 mRNA level was increased when L6 myotubes were treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
55
0
5

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(72 citation statements)
references
References 29 publications
12
55
0
5
Order By: Relevance
“…Moreover, Weigle et al [23] demonstrated that elevation of circulating free fatty acid levels induced by Intralipid plus heparin infusion mimicked the increased expression of muscle UCP3 seen after fasting. Being consistent with these in vivo results, we reported that oleic acid and a non-metabolizable α-bromopalmitic acid induced UCP3 mRNA in cultured L6 myocytes [16]. Induction of UCP2 mRNA in L6 cells was also reported by Camirand et al [4].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, Weigle et al [23] demonstrated that elevation of circulating free fatty acid levels induced by Intralipid plus heparin infusion mimicked the increased expression of muscle UCP3 seen after fasting. Being consistent with these in vivo results, we reported that oleic acid and a non-metabolizable α-bromopalmitic acid induced UCP3 mRNA in cultured L6 myocytes [16]. Induction of UCP2 mRNA in L6 cells was also reported by Camirand et al [4].…”
Section: Discussionsupporting
confidence: 91%
“…Because the β3-AR is generally recognized to be expressed in adipocytes but not in myocytes, the effect of CL in vivo is not due to a direct action of this drug on myocytes thorough the β3-AR. In fact, the UCP2 and UCP3 mRNA levels in cultured L6 myocytes were not influenced by the treatment of the cells with CL in vitro [16]. It is therefore more likely that CL stimulates UCP expression of muscle in vivo through some indirect action.…”
Section: Discussionmentioning
confidence: 93%
“…These results are in agreement with studies in vitro showing induction of UCP3 expression by RA in differentiated myotubes in cell culture. 24,25 Notwithstanding the possibility of post-transcriptional effects, the effect of retinoids on UCP3 expression may reflect enhanced activity of the retinoic acid receptor: retinoid X receptor (RAR:RXR) heterodimers and=or of peroxisome proliferator-activated receptor: RXR (PPAR:RXR) heterodimers, for both of which response elements have been described in the UCP3 gene promoter, 25,39 as well as in the UCP1 gene promoter (see ref. 1).…”
Section: Discussionmentioning
confidence: 99%
“…10,15,16,23,24 The mechanism by which PPAR ligands up-regulate UCP gene expression is complex. PPAR is a member of the nuclear receptor superfamily that includes receptors for the steroid, thyroid and retinoid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, UCP3 in L 6 myotubes has been shown to be up-regulated by thyroid hormone, ligands of peroxisome proliferator-activated receptor (PPAR) and retinoic acid. 15 Despite the increasing number of reports on UCP2 and UCP3, the molecular and=or cellular mechan-isms regulating UCP2 gene expression in skeletal muscle are still poorly understood.…”
Section: Introductionmentioning
confidence: 99%